Colonial Ghosts in Indigenous-British Conflict: A Revisiting of Two 1726 Piracy Trials - Gilhuis, Nicole (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2024)
In 1726 five men who had long been part of a Mi’kmaw community were hanged for piracy in Boston. Through an analysis of sources such as 18th-century newsletters, trial records, and genealogical data, this article addresses the debates over the place of Métis among the Mi’kmaq and the practice of Indigenous community elasticity. It also presents a new way to understand the agency, actions, and lived experience of Indigenous Acadian men – “colonial ghosts” or colonists who disappeared from the colonial record – while underlining the importance of revising imperial identity designations as well as of placing greater weight on local kinship, culture, and practice.